Topical Application of Tetrandrine Nanoemulsion Promotes the Expansion of CD4+Foxp3+ Regulatory T Cells and Alleviates Imiquimod-Induced Psoriasis in Mice - Chen, Shaokui; Lin, Zibei; He, Tianzhen; Islam, Md Sahidul; Xi, Long; Liao, Ping; Yang, Yang; Zheng, Ying; Chen, Xin (Frontiers in Immunology, 2022)
Abstract There is compelling evidence that CD4+Foxp3+ regulatory T cells (Tregs) are indispensable in the inhibition of autoimmune inflammatory responses, including psoriasis. Recently, we showed that systemically treatment with tetrandrine (TET), a two-pore channel inhibitor identified from the Chinese herb Stephania tetrandra S. Moor, could promote the proliferative expansion of Tregs in mice through stimulation of TNF-TNFR2 interaction. We thus hypothesized that topical administration of TET might also expand Tregs and consequently inhibit psoriasis. To this end, we developed a TET nanoemulsion and examined its effect on the expansion of Tregs after topical administration on mouse psoriasis induced by imiquimod. The result of our experiment showed that topical treatment with TET nanoemulsion markedly increased the proportion and number of Tregs in the spleen, as well as TNFR2 and Ki-67 expression by Tregs, in WT and TNFR1 KO mice, but not in TNFR2 KO mice. Consequently, TET nanoemulsion potently inhibited IL-17-expressing cells in the spleen and LNs of imiquimod-treated WT mice, accompanied by decreased serum levels of IL-17A, INF-γ, and TNF and their mRNA levels in the flamed lesion. Importantly, TET emulsion treatment markedly inhibited the development of psoriasis-like disease in WT and TNFR1 KO mice but not in TNFR2 KO mice. Therefore, our study indicates that the topical administration of TET could also stimulate the expansion of Tregs through the TNF-TNFR2 pathway. This effect of TET and its analogs may be useful in the treatment of inflammatory skin diseases such as psoriasis.